A Review study of Pittadhara Kala with special reference to Grahani - Sharma, Niranjan; Wane, Yogesh; Joshi, Prakash (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda was well established at the time of Samhita Kala, it was known as wonderful era of Ayurveda. This era gives great knowledge about Kala Sharir and concerned subject. In Sharir Sthan, Sushrut has described the Sapta Kala, which is an evidence of insight on microscopic level. The Kala is explained as an interface between Dhatu and Ashaya that provides a barrier between the two. Some instant Ayurvedic researcher and experts have considered only one feature of Pittadhara Kala that is digesion These seven Kala are constituted with Snayu, impregnated in Jarayu and encased in Shleshma. Healthy life depends on Samagni and root cause of all disease is Mandagni, thus being the site of Agni. Pittadhara Kala is also called as Grahani, which is the Main site of Agni as Acharyas. It occupies some important digestive part of GIT. It is correlated with mucous membrane of the part of GIT, which extend from lower part of stomach to ileocecal junction